Saving the "library of life". - Benford, G (1992)
A broad program of freezing species in threatened ecospheres could preserve biodiversity for eventual use by future generations. Sampling without studying can lower costs dramatically. Local labor can do most of the gathering. Plausible costs of collecting and cryogenically suspending the tropical rain forest species, at a sampling fraction of 10(-6), are about 2 billion dollars for a full century. Much more information than species DNA will be saved, allowing future biotechnology to derive high information content and perhaps even resurrect then-extinct species. Parallel programs of in situ and other ex situ preservation are essential to allow later expression of frozen genomes in members of the same genus. This is a broad proposal that should be debated throughout the entire scientific community.